SOCIAL INTERACTION IN THE LEARNING PROCESS ISLAMIC EDUCATION - Asia, Asia; Idi, Abdullah; Karoma, Karoma (LPPM Universitas Pahlawan Tuanku Tambusai, 2024)
This study aims to explore educational interactions in Islamic Religious Education (PAI) learning processes in schools. Using a descriptive qualitative approach, this research analyzed data from various relevant literature sources to examine the components, patterns, and factors influencing educational interactions. The findings reveal that effective educational interactions involve two-way communication between teachers and students, encompassing components such as learning objectives, methods, teaching materials, and evaluation. Teachers play a crucial role in creating a conducive learning environment, both through classroom instruction and religious activities. Educational interactions not only enhance academic understanding but also shape students' character in line with Islamic values. In conclusion, educational interactions in PAI hold significant potential for supporting students' intellectual and spiritual development